The Students’ Perception of Using ChatGPT Towards English Language Learning - Mohammad Hakamul Ulum A; Fera Zasrianita; Hanura Febriani (Yayasan Sembilan Pemuda Indonesia, 2025)
This research seeks to explore the perception of the fourth-semester Social Sciences students regarding the use of ChatGPT as a tool for English language learning at UINFAS Bengkulu, particularly concerning learning autonomy, critical thinking skills, and ethical considerations. The study utilized a descriptive qualitative method within the UTAUT2 framework. Data collection was conducted through in-depth interviews, observations, and document analysis with ten purposively sampled participants. Students largely view ChatGPT primarily as a transactional tool for quickly gaining access to vocabulary, translation, and even the completion of assignments. While there are perceived outputs and limitations such as inaccuracies (90% of respondents), risks of output creativity (70%) that are noted, there is still a practical adoption owing to the device’s usability and immediacy. Performance expectancy along with peer influence, hedonic motivation, and institutional guidance that is absent also remain as key adoption drivers. There are fears of stunting personal initiative and promoting skill stagnation through unrestricted autonomous control. This study applies UTAUT2 for the first time regarding the use of ChatGPT in learning English in a non-Western multilingual setting—Indonesia. It constructs distinct user profiles “critical pragmatists,” “intellectual minimalists and describes “critical passivity,” which is the behavioral unresponsiveness to limitations of awareness, which has not been captured in previous literature. The research results set forth tangible approaches to address the AI-academic integrity imbalance, such as the development of pedagogical frameworks incorporating AI, curricula on digital literacy, and institutional governance. This addresses the myriad shortcomings of the theories of acceptance of technology and is a contribution towards Global South educational settings grappled with AI incorporation.